Dengue Fever: Therapeutic Potential of Carica papaya L. Leaves - Sarker, Md. Moklesur Rahman; Khan, Farzana; Mohamed, Isa Naina (Frontiers in Pharmacology, 2021)
Dengue, a very widespread mosquito-borne infectious disease caused by Aedes aegypti virus, has been occurring during the monsoons every year. The prevalence and incidence of dengue fever and death due to its complications have been increased drastically in these recent years in Bangladesh, Philippines, Thailand, Brazil and India. Recently, dengue had spread in an epidemic form in Bangladesh, Thailand and Philippines. Although the infection affected a large number of people around the world, there is no established specific and effective treatment by synthetic medicines. In this subcontinent, Malaysia could effectively control its incidences and death of patients using alternative medication treatment mainly prepared from Carica papaya L. leaves along with proper care and hospitalization. Papaya leaves juice or extract as well as its different forms of preparation have been long used traditionally for treating dengue fever and its complications to save patients’ lives. Although traditional healers recommend and general people intend to use Papaya leaves juice or its other preparations in dengue fever, this treatment option is strictly denied by the physicians offering treatment in hospitals in Bangladesh as they do not believe on the effectiveness of papaya leaves, thus suggesting patients not to use it. In Bangladesh, 1,01,354 dengue patients have been hospitalized with 179 died in the year 2019 according to information from the Institute of Epidemiology, Disease Control and Research as well as the Directorate General of Health Services of Bangladesh. Most of the patients died because of the falling down of platelets to the dangerous levels and hemorrhage or serious bleeding. Therefore, this paper aims to critically review the scientific basis and effectiveness of Carica papaya L. leaves in treating dengue fever based on preclinical and clinical reports. Thrombocytopenia is one of the major conditions that is typical in case of dengue infection. Besides, the infection and impairment of immunity are concerned with dengue patients. This review summarizes all the scientific reports on Carica papaya L. for its ability on three aspects of dengue: antiviral activities, prevention of thrombocytopenia and improvement of immunity during dengue fever.